Plant-Parasitic Nematodes : A Pictorial Key to Genera - Mai, William (Book collections on Project MUSE., 1996)
Formerly titled Plant-Parasitic Nematodes: A Pictorial Key to Genera, this volume has been the standard work on plant disease around the globe. Now in its fifth edition, it remains the fundamental reference for students as well as for ...